Tiberius. - Seager, Robin (Blackwell ancient lives., 2007)
Robin Seager has updated his classic biography of Tiberius, which focuses on the Emperor's complex character as the key to understanding his reign.:.; The most readable account available of the life of Tiberius, the second Roman emperor.; Argues that Tiberius' character provides the key to understanding his reign.; Portrays Tiberius as a man whose virtues and beliefs were corrupted by power.; Shows how Tiberius' fears of conspiracy and assassination caused him to lose his grasp of reality.; A new afterword discusses important new evidence that has come to light on the reign of Tiberius.